Development of the calculation method of complex acoustic resonator parameters - Богданов, Микола Юрійович; Кірчу, Федір Іванович (Eastern-European Journal of Enterprise Technologies, 2015)
Despite the large number of works devoted to passive management methods of separated flows in the stages of axial fans, still little attention has been paid to the integrated approaches of impact on the end separated flows. In the paper, the calculation method of complex resonator parameters based on the method of hydro-gas-dynamic analogies was presented. The basic idea of using the complex resonator is pulse-periodic action on the end separated eddy flows, which consist of high-frequency and low-frequency components of oscillations. The paper presents the formation of generalized dependencies for calculating geometrical parameters of the complex resonator, which consists of two series-connected acoustic cavities, one of which is tuned to the high frequency component, and the other - to the low-frequency component of the oscillation field. The presented method allows to obtain the relationship between the geometric parameters of the complex acoustic resonator and the frequency of its natural oscillations. The research results can be used in the design of control systems of separated flows in the turbomachinery blade rows.